Positive swim pacing improves subsequent sprint distance triathlon performance in well-trained athletes - Wu, S.; Peiffer, J.; Peeling, P.; Brisswalter, J.; Lau, W. Y.; Nosaka, K.; Abbiss, C. (Journal of Science and Medicine in Sport, 2016)
Background: Triathlon is a multi-sport event that consists of sequential swim, cycle and run disciplines. The manipulation of pacing during triathlon is crucial to performance but complex due to the importance of optimising energy expenditure throughout the three different locomotion modes.